COMMUNITY BASED COASTAL CONSERVATION: CASE STUDY ON NATURE CONSERVATION FORUM PUTRI MENJANGAN, BULELENG, BALI - I Nyoman Januarsa; Oktiyas Muzaky Luthfi (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2017)
Conservation is one form of natural resource management have been damaged. There are many types of area management one of which is community base management. Nature Conservation Forum Putri Menjangan is a group of people who have an interest in the management of natural resources, especially on mangrove ecosystems and coral reef ecosystems, in addition to conservation activities are also carried out data collection species start from mangrove, coral reef, reef fishes and other organisms that live in Putri Menjangan waters. Mangrove forest conservation is done through reforestation in areas which have a low mangrove cover, whereas for coral reef conservation activities carried out through coral transplantation and garbage clean up activity in coral reef ecosystems both of trash and competitor organism found on coral reef ecosystems.Keywords: reforestation, transplantation, clean up